Cave and worship in Ancient Greece
1 online resource (xviii, 252 pages)
Keywords: Cave and Worship in Ancient Greece brings together a series of stimulating chapters contributing to the archaeology and our modern understanding of the character and importance of cave sanctuaries in the fi rst millennium BCE Mediterranean. Written by emerging and established archaeologists and researchers, the book employs a fascinating and wide range of approaches and methodologies to investigate, and interpret material assemblages from cave shrines, many of which are introduced here for the fi rst time. An introductory section explores the emergence and growth of caves as centres of cult and religion. The chapters then probe some of the meanings attached to cave spaces and votive materials such as terracotta fi gurines, and ceramics, and those who created and used them. The authors use sensory and gender approaches, discuss the identity of the worshippers, and the contribution of statistical analysis to the role of votive materials. At the heart of the volume is the examination of cave materials excavated on the Cycladic islands and Crete, in Attika and Aitoloakarnania, on the Ionian islands and in southern Italy. This is a welcome volume for students of prehistoric and classical archaeology,enthusiasts of the history of caves, religion, ancient history, and anthropology.